Color intrigue optical anti-counterfeiting alumite and production process thereof

Through multi-layer structural design and advanced processes, electroplated aluminum material achieves a synergistic enhancement effect of dual temperature and magnetic field response, solving the problems of independent functional layers and easy counterfeiting in existing electroplated aluminum materials for multi-functional anti-counterfeiting. It has precise and controllable hot stamping peeling force and machine-readable infrared invisible anti-counterfeiting features, improving the stability and security of anti-counterfeiting materials.

CN121671206APending Publication Date: 2026-03-17TANN SHANGHAI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610143169.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-02-02
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing electroplated aluminum materials have problems in multi-functional anti-counterfeiting, such as independent functional layers, easy counterfeiting, weak interlayer bonding, poor response effect and poor stability, making it difficult to achieve integrated machine-readable advanced anti-counterfeiting features.

Method used

It adopts a multi-layer structure design, including a magnetically sensitive enhanced substrate layer, a temperature-sensitive phase change separation layer, a temperature-magnetic composite nanofiber iridescent layer, a polyelectrolyte barrier layer, and a gradient magnetically sensitive aluminum-plated layer. Through in-situ composite processes such as microfluidics and electrospinning, it achieves a synergistic enhancement effect of dual temperature and magnetic field responses, and embeds an infrared invisible identifier.

Benefits of technology

It realizes a multi-level three-dimensional anti-counterfeiting system that can dynamically change color from the naked eye to magneto-gloss, and has precise and controllable hot stamping peel force and machine-readable infrared invisible anti-counterfeiting features, thereby improving the stability and security of anti-counterfeiting materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121671206A_ABST
    Figure CN121671206A_ABST
Patent Text Reader

Abstract

The invention discloses multicolor optical anti-counterfeiting alumite and a production process thereof. The alumite sequentially comprises a magnetic-sensitive enhanced substrate layer, a dynamic separation layer, a temperature-magnetic composite nanofiber multicolor layer, a polyelectrolyte alternate deposition barrier layer and a gradient magnetic-sensitive aluminized layer from bottom to top, wherein the magnetic-sensitive enhanced substrate layer, the dynamic separation layer, the temperature-magnetic composite nanofiber multicolor layer, the polyelectrolyte alternate deposition barrier layer and the gradient magnetic-sensitive aluminized layer are arranged on the alumite; wherein the magnetic-sensitive enhanced substrate layer comprises a graphene modified PET supporting layer and a three-dimensional net-shaped micro-channel embedded with Fe3O4 particles, the dynamic separation layer is temperature-sensitive phase change fluororesin, the temperature-magnetic composite nanofiber colorful layer is electrostatic spinning nanofibers of a core-sheath structure, and the blocking layer is of a polyelectrolyte alternate deposition structure and is embedded with infrared invisible identification particles. According to the invention, four anti-counterfeiting functions of multicolor optical response, magnetic response activation and infrared invisible two-dimensional codes are integrated, the advantages of high multicolor optical contrast, fast response, multiple reuse times, excellent barrier performance, stable transfer printing and the like are achieved, the method is suitable for scenes of high-end tobacco and wine, luxury packaging, high-added-value labels and the like, and the anti-counterfeiting grade and the practicability are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electroplated aluminum technology, specifically, it relates to a holographic optical anti-counterfeiting electroplated aluminum and its production process. Background Technology

[0002] Hot stamping foil (foil foil) is a high-end surface decoration and anti-counterfeiting material widely used in packaging printing, textiles, plastic products and other fields. Traditional hot stamping foil usually consists of a base film, a release layer, a coloring layer (or functional layer), an aluminum plating layer and an adhesive backing layer. The aluminum plating layer and the pattern are transferred to the substrate through a hot stamping process.

[0003] As market demands for product anti-counterfeiting and security increase, simple visual decorations or static anti-counterfeiting features are no longer sufficient. Currently, some electroplated aluminum alloys with thermochromic, photochromic, or magnetic response functions have emerged on the market. However, these solutions typically suffer from one or more of the following problems: most products only have a single response mode (e.g., only thermochromic or only magnetic), resulting in insufficient anti-counterfeiting layers and susceptibility to counterfeiting. Furthermore, even when multiple functions are integrated, the functional layers are often independent, lacking synergistic enhancement effects, leading to poor overall response or instability. Simultaneously, to achieve multi-functionality, simple physical coating or composite methods are often used, resulting in weak interlayer adhesion. During hot stamping, incomplete transfer and pattern defects are prone to occur, ultimately producing anti-counterfeiting features that are mostly visible to the naked eye, making it difficult to integrate machine-readable, highly concealed advanced anti-counterfeiting information.

[0004] Therefore, developing a high-end electroplated aluminum material that integrates multiple dynamic responses, synergistic functions of each layer, stable and reliable structure, and stealth anti-counterfeiting capabilities has significant industrial value and market prospects. Summary of the Invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a holographic optical anti-counterfeiting electroplated aluminum and its production process, which can not only produce significant and synergistically enhanced holographic optical changes under temperature and magnetic field stimulation, but also has precise and controllable hot stamping peeling force and machine-readable infrared invisible anti-counterfeiting features, realizing a multi-level anti-counterfeiting system from public recognition to professional authentication.

[0006] To achieve the above-mentioned technical objectives, this invention discloses a multi-layered electroplated aluminum foil with iridescent optical anti-counterfeiting features. The electroplated aluminum foil comprises, from bottom to top (i.e., from the side furthest from the substrate to the side closest to the substrate): Magnetic-Sensitive Enhanced Substrate Layer: Serving as the supporting foundation for the entire material and providing primary magnetic response, this layer is a composite of a modified PET support layer and a three-dimensional mesh microchannel layer constructed upon it. The modified PET support layer is a biaxially stretched PET film doped with 3%-5% by mass graphene, with a thickness of 25-30 μm, significantly improving the substrate's mechanical strength (tensile strength ≥180 MPa) and dimensional stability. The three-dimensional mesh microchannel layer is formed in situ on the PET film surface using microfluidic molding technology. Its microchannels are a three-dimensional interwoven mesh with randomly distributed pore sizes of 5-20 μm and a porosity of 30%-45%. These microchannels are filled with Fe3O4 magnetic sensitive particles with a particle size of 20-50 nm, at a mass fraction of 8%-12%, imparting a saturation magnetization of 50-80 emu / g to the substrate layer. This structure enhances the mechanical anchoring of the substrate to the subsequent functional layers and provides a uniformly distributed magnetic response source.

[0007] Dynamic release layer: Directly laminated onto the base layer, its function is to provide temperature-adaptive peel force during hot stamping. This layer consists of a single thermosensitive phase-change fluoropolymer resin, with a thickness of 1.5-2.0 μm. Its main components are a blend of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) and polyethylene glycol (PEG) with a mass fraction of 5%-8% and a phase change temperature of 48℃. At room temperature (<45℃), this layer has a peel force of 0.5-0.7 N / cm, ensuring the stability of the electroplated aluminum coil. When the hot stamping temperature reaches 45-55℃, PEG undergoes a solid-liquid phase change, causing a sharp decrease in the cohesive force of the resin layer, and the peel force adaptively drops to 0.1-0.2 N / cm. This allows for precise and complete transfer of the aluminum plating layer and the iridescent layer under extremely low pressure, achieving a heat transfer success rate of over 99.8%.

[0008] Temperature-magnetic composite nanofiber iridescent layer: As the core iridescent optical response functional layer, it is directly constructed on top of the release layer. This layer is formed by in-situ deposition of temperature-magnetic composite nanofibers with a core-sheath structure through electrospinning, with a thickness of 4-6 μm and an areal density of 8-12 g / m³. 2The core layer is a thermosensitive color-changing core material, using a color-changing dye grafted with N-isopropylacrylamide-maleic anhydride copolymer. It can achieve continuous and reversible iridescent color changes within a wide temperature range of 12-75℃, with a response time ≤4s and a repeatable color change count ≥6000 times. The sheath layer is a magnetically sensitive polymer matrix, composed of PVDF-HFP blended with 10%-15% Fe3O4 nanoparticles by mass. The nanofiber diameter is distributed in a gradient of 500-2000nm, the core layer diameter is 200-800nm, and the sheath thickness is 150-600nm. This unique structure allows an external magnetic field (100-300mT) to not only act on the sheath layer but also synergistically influence the molecular arrangement or microenvironment of the core layer dye through a magneto-mechanical-thermal effect, thereby improving the iridescent optical contrast by more than 50% and achieving a significant enhancement of the magnetic-thermal effect.

[0009] Alternating Polyelectrolyte Deposition Barrier Layer: Located above the iridescent layer, this layer combines physical barrier properties with advanced optical anti-counterfeiting features. It is formed by alternating deposition of 15-25 layers of polycationic electrolytes (such as polyallylamine hydrochloride, PAH) and polyanionic electrolytes (such as sodium polystyrene sulfonate, PSS) using a layer-by-layer self-assembly technique, resulting in a total thickness of 2.0-3.5 μm. During assembly, antimony-doped tin oxide (ATO) nanoparticles (3%-6% by mass) with a particle size of 80-150 nm are embedded into the electrolyte network. ATO particles exhibit characteristic absorption peaks in the 8-14 μm infrared band, which can display pre-arranged patterns such as QR codes under infrared thermal imaging with a recognition accuracy ≥99%, providing concealed anti-counterfeiting information for machine identification. This dense multilayer structure also effectively blocks moisture and oxygen, protecting the underlying iridescent material.

[0010] Gradient magnetron-sensitive aluminum plating layer: Located on the outermost layer, it provides a decorative iridescent metallic luster and possesses dynamic magneto-optical response characteristics. This layer is fabricated using a magnetron sputtering process and includes: Magnetic-sensitive transition layer: 0.05-0.1μm thick, doped with CoNiP alloy nanoparticles with a particle size of 10-30nm and a mass fraction of 8%-12%, which enhances the bonding force with the underlying polymer and introduces magnetic sensitivity.

[0011] Gradient aluminum film layer: 0.12-0.18μm thick, with aluminum content gradually increasing from 95% near the transition layer to 100% on the upper surface through precise control of sputtering process parameters. This film layer has a density ≥99.9%, a surface roughness Ra≤0.008μm, and high gloss. Under an external magnetic field of 0.3-0.8T, the iridescent metallic reflectivity of the aluminum coating layer can dynamically change by ≥30%, forming a unique visual anti-counterfeiting feature.

[0012] This invention also discloses a production process for iridescent optical anti-counterfeiting electroplated aluminum, which is a continuous integrated production line, mainly including the following steps: S1. Substrate Pretreatment The graphene-modified PET substrate is unwound and treated using a plasma-UV composite treatment device (e.g., 500-600W plasma with 80-100mW / cm²). 2 The treatment atmosphere was Ar:O2=4:1, and the treatment speed was 3-6 m / min. This reduced the contact angle of the substrate surface to below 20°, greatly improving its surface energy and reactivity.

[0013] S2. Formation of the magnetically enhanced substrate layer A PDMS microfluidic chip with a specific channel pattern (channel width 5-20 μm, depth 8-15 μm) is bonded to a pretreated substrate, and a 10%-15% (w / w) Fe3O4 nanoparticle dispersion is injected. Capillary action and microfluidic forces are used to fill and solidify the dispersion into a three-dimensional microchannel network formed on the substrate surface. After vacuum drying at 60-80℃ for 2-3 hours, a robust magnetically enhanced substrate layer is formed.

[0014] S3. Coating and curing of the dynamic release layer On the magnetically enhanced substrate, a temperature-sensitive phase change fluoropolymer slurry (a mixed solution of PVDF-HFP and PEG) is precisely coated, and then segmented thermosetting is performed: first, it is treated at 80°C for 1.5 minutes to allow the solvent to evaporate and form a preliminary film, and then treated at 130°C for 2 minutes to allow the resin to fully cure and form a stable phase change structure.

[0015] S4. Electrospinning of the iridescent layer of temperature-magnetic composite nanofibers A coaxial electrospinning apparatus was used to inject the inner spinning solution (8%-12wt% of a thermosensitive color-changing core material solution, with DMF / acetone as the solvent) and the outer spinning solution (15%-20wt% of a PVDF-HFP solution containing Fe3O4, with Fe3O4 requiring ultrasonic-magnetic field synergistic dispersion pretreatment) into the inner and outer needles, respectively. Under controlled conditions of spinning voltage 18-25kV, receiving distance 15-20cm, feed speed 0.5-1.0 mL / h, and ambient temperature and humidity (25-30℃, 40-50% RH), core-sheath structured nanofibers were directly spun and received on the surface of the dynamic release layer. Subsequently, heat setting at 100℃ for 1 minute was performed to enhance the interfiber bonding force.

[0016] S5. Layer-by-layer self-assembly of polyelectrolyte barrier layers The substrate with the iridescent layer is immersed in a 2%-3wt% PAH solution (polycationic) for 3-5 minutes, then removed, cleaned, and dried. It is then immersed in a 1.5%-2.5wt% PSS solution containing ATO nanoparticles (polyanionic) for the same time, removed, cleaned, and dried to complete the deposition of one bilayer. This process is repeated 15-25 times. To enhance interlayer bonding, a brief UV curing (365nm, 50mW / cm²) is performed after every 5 layers. 2 (30s). ATO nanoparticles need to be pre-treated by ball milling (300 r / min, 2h) before deposition to ensure uniform dispersion (particle size variation coefficient ≤8%).

[0017] S6. Magnetron sputtering of gradient magnetically sensitive aluminum coating In an ultra-high vacuum environment (1×10 -5 -5×10 -5 The process employs dual-target magnetron sputtering. First, a CoNiP alloy target (300-500W power) is used for sputtering for 10-15 seconds to deposit a magnetically sensitive transition layer on the barrier layer surface. Then, an aluminum target is used for sputtering. During the 20-30 second deposition time, the power of the aluminum target is linearly increased from 800W to 1500W via a closed-loop control system. The sputtering gas is Ar:He = 3:2, thereby depositing a dense aluminum film with an aluminum content gradually increasing from 95% to 100% on the transition layer. The final product is then wound up after online quality inspection (including magnetic response intensity, infrared identification rate, etc.).

[0018] Compared with the prior art, the present invention can achieve the following technical effects: Through an innovative design integrating a magnetically enhanced substrate, a temperature-sensitive phase change release layer, a core-sheath composite nanofiber iridescent layer, a polyelectrolyte barrier layer embedded with infrared markings, and a gradient magnetically sensitive aluminized layer, a synergistic enhancement effect of dual temperature and magnetic field response signals is achieved. This constructs a multi-level, three-dimensional anti-counterfeiting system that ranges from visually iridescent color changes and dynamic changes in magnetostrictive luster to instrument-readable infrared invisible QR codes. Its temperature-sensitive phase change release layer enables adaptive adjustment of the peeling force, ensuring a high success rate for high-precision hot stamping. Furthermore, the in-situ composite of each functional layer through microfluidic and electrospinning processes ensures high stability and long-life cycle performance of the overall structure. This material combines superior dynamic anti-counterfeiting functionality, reliable practical performance, and the outstanding advantage of being mass-produced through an integrated process, significantly raising the technological level and security threshold of high-end anti-counterfeiting packaging materials.

[0019] Of course, any product implementing this invention does not necessarily need to achieve all of the technical effects described above at the same time. Attached Figure Description

[0020] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this invention, illustrate exemplary embodiments of the invention and are used to explain the invention, but do not constitute an undue limitation of the invention. In the drawings: Figure 1 is a schematic diagram of the layered structure of the iridescent optical anti-counterfeiting electroplated aluminum of the present invention.

[0021] Figure 2 is a schematic diagram of the core-sheath structure of the fibers in the iridescent layer of the thermo-magnetic composite nanofiber of the present invention.

[0022] Figure 3 is a schematic diagram of the integrated production process of the present invention.

[0023] Figure label: 1 - Magnetic-sensitive enhanced substrate layer; 1a - Modified PET support layer; 1b - Three-dimensional mesh microchannel layer and Fe3O4 particles; 2 - Dynamic detachment layer; 3 - Thermo-magnetic composite nanofiber iridescent layer; 4 - Polyelectrolyte alternating deposition barrier layer; 5 - Gradient magnetic-sensitive aluminum plating layer; 5a - Magnetic-sensitive transition layer; 5b - Gradient aluminum film layer. Detailed Implementation

[0024] The following will describe in detail the implementation of the present invention with reference to the accompanying drawings and embodiments, so that the process of how the present invention uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0025] First, please refer to Figure 1, which shows a schematic cross-sectional view of the complete layered structure of the temperature-magnetic dual-response anti-counterfeiting holographic optical anti-counterfeiting electroplated aluminum of the present invention. As shown in Figure 1, the present invention is a precision multilayer composite film, which is stacked sequentially from the side away from the substrate (bottom) to the side about to be transferred to the substrate (top), forming a functionally synergistic whole. The specific layers are as follows: Magnetic-Sensitive Enhanced Substrate Layer 1: This layer provides mechanical support and serves as the primary magnetic functional layer for the entire material. It is composed of two composite parts: a modified PET support layer 1a, a three-dimensional mesh microchannel layer constructed on top of it, and Fe3O4 magnetic-sensitive particles 1b filling the mesh. The modified PET support layer 1a provides basic strength and flexibility, while the three-dimensional mesh microchannel layer and Fe3O4 particles 1b, through their micro-nano structure, significantly increase the specific surface area and form a physical anchor with the subsequent layers. At the same time, the uniformly distributed Fe3O4 particles endow the substrate with intrinsic magnetic responsiveness.

[0026] The dynamic release layer 2 is attached to the magnetically enhanced substrate layer 1. This layer is composed of a temperature-sensitive phase change fluoropolymer, and its core function is that during the heat transfer process, its peel strength can undergo intelligent and reversible dramatic changes according to the temperature (especially the set hot stamping temperature), thereby ensuring that the decorative layer is completely and accurately peeled off and transferred under optimal conditions.

[0027] The thermochromic composite nanofiber iridescent layer 3 is grown in situ on the dynamically detached layer 2 using electrospinning technology, and is composed of countless interwoven nanofibers with special structures. Please refer to Figure 2, which shows a schematic diagram of the microscopic core-sheath structure of the composite nanofiber. The core layer is mainly composed of thermochromic materials, responsible for changing iridescent colors in response to temperature changes; the sheath layer is composed of a polymer matrix doped with a high content of Fe3O4 nanoparticles, which not only protects the core layer and improves stability, but more importantly, endows the fiber with strong magnetic responsiveness. The magnetic field can affect the sheath layer, thereby synergistically modulating the color-changing behavior of the core layer, producing a "1+1>2" enhancement effect.

[0028] An alternating polyelectrolyte deposition barrier layer 4 is deposited on top of the thermo-magnetic composite nanofiber iridescent layer 3, serving a dual function. First, its dense nanolayered structure effectively blocks environmental factors such as moisture and oxygen from eroding the underlying sensitive iridescent material, significantly improving product durability. Second, during this layer-by-layer assembly process, infrared stealth marker particles (such as ATO) are intentionally embedded. These particles are transparent under visible light but have characteristic responses in specific infrared bands, which can be encoded into machine-readable patterns (such as QR codes), forming a sophisticated and concealed anti-counterfeiting barrier with high anti-counterfeiting capabilities.

[0029] The gradient magnetically sensitive aluminum plating layer 5, serving as the outermost decorative and functional layer, directly determines the product's iridescent metallic appearance and another dynamic anti-counterfeiting feature. This layer is also a composite structure, including: a magnetically sensitive transition layer 5a, containing magnetic alloy nanoparticles such as CoNiP, used to enhance the bonding force with the underlying polymer and introduce magnetic sensitivity; and a gradient aluminum film layer 5b, whose aluminum purity is not constant, but rather increases continuously from the interface to the surface (e.g., 95%→100%). This gradient design optimizes the film's density and bonding force. More importantly, under the influence of an external magnetic field, its iridescent metallic luster (reflectivity) exhibits observable dynamic changes, becoming another intuitive and difficult-to-imitate anti-counterfeiting feature.

[0030] The preparation process of this invention is a continuous, integrated precision manufacturing process, as illustrated in Figure 3 as a block diagram. The entire process begins with substrate unwinding and proceeds sequentially as follows: S1 Substrate pretreatment; S2 Microfluidic molding to construct a magnetically enhanced substrate layer; S3 Coating and curing a dynamic release layer; S4 Electrospinning to construct a thermo-magnetic composite nanofiber iridescent layer; S5 Layer-by-layer self-assembly deposition of a barrier anti-counterfeiting layer; S6 Magnetron sputtering to prepare a gradient magnetically sensitive aluminum plating layer; and finally, online inspection and winding. This process ensures interfacial integration and performance consistency between the functional layers.

[0031] The following three examples, each with a different focus, illustrate how to customize product performance by adjusting material formulations and process parameters, and demonstrate its superior effects.

[0032] Example 1: General-purpose high magnetic response, wide temperature range iridescent optical anti-counterfeiting electroplated aluminum The goal of this embodiment is to prepare a general-purpose product that is suitable for most packaging anti-counterfeiting scenarios, has balanced and outstanding performance, strong magnetic response, wide temperature range of iridescent optical response, and obvious anti-counterfeiting features.

[0033] The substrate is a commercially available functional PET film with a thickness of 30.0 ± 0.5 μm. During the production process, 4.0 wt% of high-quality graphene nanosheets (sheet diameter 1-5 μm, thickness 3-8 nm) are uniformly incorporated into the film. Laboratory tests show that its longitudinal tensile strength is ≥195 MPa, elongation at break is approximately 120%, and heat shrinkage (150℃, 30 min) is ≤1.0%. Surface tension is ≥50 mN / m.

[0034] Magnetic sensitive particles: Monodisperse Fe3O4 nanospheres synthesized via a hydrothermal method, with an average particle size of 35±5 nm. Measurements using a vibrating sample magnetometer (VSM) showed a saturation magnetization (Ms) of 78 emu / g and a coercivity (Hc) less than 10 Oe, exhibiting good superparamagnetic properties. Prior to use, surface modification with oleic acid was performed to improve their dispersion stability in organic solvents and subsequent polymer matrices.

[0035] Dynamic release layer resin: The main polymer is polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP, with HFP content of approximately 12%), providing excellent chemical inertness, weather resistance, and film-forming properties. The phase change material is polyethylene glycol (PEG-4000) with an average molecular weight of 4000 and a melting range (phase change temperature) of 47-49℃.

[0036] Temperature-magnetic composite nanofiber materials: Core layer (thermosensitive core material): A copolymer of N-isopropylacrylamide (NIPAM) and maleic anhydride (MA) (P(NIPAM-co-MA)) was synthesized via free radical polymerization at a molar ratio of 97:3. This copolymer has a low critical solution temperature (LCST) of approximately 32°C in aqueous solution. Then, a spiropyran thermochromic dye (with a chromatic optical response range of 20°C to 70°C, and a color transition from deep blue to colorless or light yellow) was covalently grafted onto the side chains of the polymer via an amidation reaction. The final product was dissolved in N,N-dimethylformamide (DMF) to prepare a spinning solution A with a solid content of 10 wt%.

[0037] Sheath (magnetic matrix): PVDF-HFP was dissolved in a mixed solvent of DMF and acetone (volume ratio 7:3) to prepare an 18 wt% solution. Then, under vigorous stirring and ultrasonic (600W) assistance, 15.0 wt% of the above-mentioned oleic acid modified Fe3O4 nanoparticles (based on the solid mass of PVDF-HFP) were slowly added. To break the soft agglomeration of nanoparticles, an ultrasonic-magnetic field synergistic dispersion method was used: the mixture was placed in an ultrasonic bath with a frequency of 40 kHz, and a transverse alternating magnetic field of 0.25 T was applied simultaneously for a total treatment time of 40 minutes, resulting in a uniform and stable black spinning solution B.

[0038] Barrier layer material: Polyelectrolytes: polyallylamine hydrochloride (PAH, Mw ≈ 70,000), sodium polystyrene sulfonate (PSS, Mw ≈ 70,000).

[0039] Infrared labeled particles: Commercially purchased antimony-doped tin oxide (ATO) nanoparticles with an average particle size of 120 nm and an Sb doping content of 10 at.%. Before use, the particles were dispersed and refined using a planetary ball mill (zirconia balls, 300 rpm, 2 hours) to ensure that the coefficient of variation (Cv) of particle size distribution was less than 10%.

[0040] Coating targets: High-purity aluminum target (purity 99.999%); CoNiP alloy target (composition: Co 50 at.%, Ni 45 at.%, P 5 at.%).

[0041] Key process equipment includes a roll-to-roll atmospheric plasma treatment machine (equipped with a medium-frequency power supply and 185 / 254nm UV lamps), a precision micro-gravure coating machine, a coaxial electrospinning wide-width receiving device (working width up to 800mm), a fully automatic dip-pull layer-by-layer self-assembly machine (with temperature control and online UV curing module), and a large-scale roll-to-roll high-vacuum magnetron sputtering coating system.

[0042] The specific process is as follows: Step S1: Substrate Pretreatment Graphene-modified PET substrate was unwound and conveyed at a constant speed of 5.0 m / min. First, it passed through a 580 W atmospheric pressure argon / oxygen mixed gas plasma zone (Ar:O2=85:15, total flow rate 120 sccm), where high-energy particles and active free radicals physically bombarded and chemically activated the PET surface, etching the weak boundary layer and introducing polar functional groups (-COOH, -OH). Immediately afterwards, the substrate was irradiated with ultraviolet light, primarily at a wavelength of 254 nm (irradiance 95 mW / cm²).2 Ultraviolet light further cleans the surface and promotes the cross-linking reaction, stabilizing the pretreatment effect. After treatment, the surface water contact angle was measured using a contact angle meter, showing a sharp decrease from the original approximately 78° to 16°, with a calculated surface energy as high as 59 mN / m. This superhydrophilic surface greatly facilitates subsequent processing with water-based or polar solvents, ensuring uniform coating spread and strong adhesion.

[0043] Step S2: Constructing a magnetically enhanced substrate layer In this step, the present invention designed and fabricated a polydimethylsiloxane (PDMS) soft template with a biomimetic random network structure. The microchannel network on the template has a Gaussian random distribution of channel width in the range of 5-20 μm and a channel depth of 12 μm. The pretreated PET substrate is precisely aligned with the PDMS template and lightly pressed together. Subsequently, a prepared water-based dispersion of Fe3O4 nanoparticles (containing 0.5% sodium polyacrylate dispersant) with a mass fraction of 12% is injected into the microchannel system. Driven by capillary force and assisted by a slight external negative pressure (-5 kPa), the dispersion is rapidly and completely absorbed and fills the entire three-dimensional network.

[0044] After filling, the composite was placed in a temperature-controlled vacuum drying oven. The drying program was as follows: the temperature was increased from room temperature to 60°C at a rate of 2°C / min and maintained at this temperature for 1 hour, while maintaining a vacuum of -0.09 MPa to slowly remove moisture; then the temperature was increased to 80°C and maintained for 2 hours to ensure complete drying. After drying, the PDMS template was carefully peeled off, resulting in a firmly adhered, regularly morphologically regular three-dimensional network composite structure layer on the PET substrate surface. Scanning electron microscopy (SEM) cross-sectional observation showed that Fe3O4 particles were firmly locked within the microchannels, and the porosity of the resulting composite layer was approximately 38%. VSM testing showed that the saturation magnetization of this magnetically enhanced substrate layer reached 65 emu / g, providing a solid foundation for subsequent magnetic response.

[0045] Step S3: Applying and curing the dynamic release layer PVDF-HFP particles were dissolved in DMF to prepare a 20 wt% stock solution. Accurately weighed PEG-4000 (7.0% of the PVDF-HFP solid mass) was added to the stock solution under vigorous stirring in a 60°C water bath, and the mixture was stirred for 6 hours until a homogeneous, transparent, viscous slurry was formed.

[0046] The slurry was transferred to the surface of the magnetically enhanced substrate layer (1) using microgravure coating technology. The wet film thickness was controlled at 3.8 ± 0.2 μm by precisely controlling the depth of the gravure cells and the doctor blade pressure. The coated material immediately entered a multi-stage hot air drying channel. The first stage was set at 80°C, and the conveyor belt speed kept the material in place for about 100 seconds. The main purpose of this stage was to allow most of the DMF solvent to evaporate slowly, prevent surface skinning, and form a preliminary continuous film. The temperature of the second stage was raised to 130°C and held for about 120 seconds. This high-temperature stage not only completely removed the residual solvent but also promoted the crystallization of PVDF-HFP and formed a stable phase separation structure in the PEG microregions, thereby "locking in" its phase change properties. The thickness of the dynamic release layer after curing was about 1.9 μm. The peel strength was 0.66 N / cm at room temperature of 25°C when tested using a 90° peel tester. When the temperature of the heating stage was raised to 52°C (above the phase transition point of PEG), the peel strength dropped rapidly to 0.15 N / cm within 3 seconds.

[0047] Step S4: Electrospinning to construct a thermo-magnetic composite nanofiber iridescent layer This step uses a coaxial spinning needle (inner diameter 21G, outer diameter 16G). Spinning solution A (core layer) is loaded into the inner injection pump, with a feed rate set to 0.35 mL / h; spinning solution B (sheath layer) is loaded into the outer injection pump, with a feed rate set to 0.75 mL / h. The receiving device (i.e., the substrate already coated with the release layer) is grounded, and a 22 kV DC high voltage is applied between the needle and the receiving substrate. The distance between the needle tip and the surface of the receiving substrate (receiving distance) is set to 18 cm. The entire spinning process is carried out in a temperature and humidity-controlled chamber, with the ambient temperature maintained at 28±1℃ and the relative humidity controlled at 45±3%.

[0048] Under a high electrostatic field, coaxial droplets are stretched into Taylor cones, forming a continuous composite jet with a clear core-sheath structure. During its flight, the jet undergoes intense whipping, stretching, and solvent evaporation, eventually solidifying and depositing on the receiving substrate to form a nonwoven fiber membrane. By controlling the moving speed of the receiving substrate and the spinning time, a uniform fiber layer with a thickness of 5.1 ± 0.3 μm can be obtained. The fiber diameter exhibits a good gradient distribution, and the surface is smooth without obvious beading. Transmission electron microscopy (TEM) section observation clearly distinguishes the boundary between the core and sheath layers, with the core layer diameter approximately 300-700 nm.

[0049] After spinning, the material immediately passes through a hot press roller with a surface temperature of 100°C for approximately 1 second. This heat setting process causes a slight melting and adhesion between adjacent fibers at the contact point, significantly improving the mechanical integrity and interlayer bonding of the fiber web without affecting its porous structure and responsiveness.

[0050] Step S5: Layer-by-layer self-assembly deposition of barrier anti-counterfeiting layer A 2.5 wt% PAH aqueous solution and a 2.0 wt% PSS aqueous solution were prepared, both with ionic strength adjusted to 0.15 M using sodium chloride. Pre-treated ATO nanoparticles, ball-milled, were added to the PSS solution to achieve a mass concentration of 1.0 wt% (relative to the PSS solution).

[0051] An automated dip-and-pull system was used for the operation. A complete "bilayer" deposition cycle is as follows: 1) The substrate is immersed in a PAH solution for 300 seconds, allowing positively charged PAH molecular chains to adsorb onto the negatively charged iridescent layer surface via electrostatic attraction; 2) After removal, the substrate is rinsed for 20 seconds in each of three series-connected ultrapure water rinsing tanks to remove physically adsorbed molecules; 3) The surface is dried with clean nitrogen gas; 4) The substrate is immersed in a PSS solution containing ATO for 300 seconds, allowing negatively charged PSS molecules and ATO particles to adsorb onto the PAH layer; 5) The rinsing and drying steps are repeated. At this point, a (PAH / PSS+ATO) bilayer is assembled.

[0052] To enhance the film's adhesion, after every five such double-layer cycles (i.e., 10 layers), the substrate is briefly moved through a power density of 50 mW / cm². 2 Irradiation was performed for 30 seconds under a UV LED lamp (main wavelength 365 nm). The UV light can induce cross-linking of the small number of photosensitive groups that may exist in the PSS, thereby "pinning" the deposited layered structure and preventing it from peeling off during subsequent deposition or use.

[0053] The above cycle was repeated 20 times, ultimately depositing 40 molecular layers to form a polyelectrolyte alternating deposition barrier anti-counterfeiting layer with a total thickness of approximately 3.2 μm. X-ray photoelectron spectroscopy (XPS) depth profiling confirmed the presence of antimony (Sb), indicating successful ATO particle embedding. This layer exhibits high transmittance in the visible light region, does not affect the iridescent effect of the underlying layer, but possesses excellent water-blocking properties (water vapor transmittance < 5 g / m²). 2 ・day).

[0054] Step S6: Prepare gradient magnetically sensitive aluminum layer by magnetron sputtering The material with the completed barrier layer coating is loaded into the unwinding chamber of a large-scale wound magnetron sputtering equipment. The system background vacuum is then evacuated to a value better than 2 × 10⁻⁶. -5 Pa.

[0055] Deposition of the magnetically sensitive transition layer: High-purity argon (Ar) gas is introduced into the vacuum chamber, and the working pressure is stabilized at 0.25 Pa. The power supply to the CoNiP alloy target is turned on, and the DC power is set to 420 W. The unwinding and rewinding system is started, allowing the substrate to pass through the sputtering area at a uniform speed of 0.8 m / min. By controlling the sputtering time and substrate travel speed, a CoNiP alloy film with a thickness of approximately 0.07 μm is deposited on the barrier layer surface. This layer provides good nucleation sites for subsequent aluminum deposition and is also magnetic.

[0056] Deposition of gradient aluminum film: The CoNiP target was shut down and switched to the aluminum target. The process gas was changed to a mixture of Ar and helium (He) (flow rate ratio Ar:He = 3:2). The addition of He helped to obtain a denser film at low pressure. At the start of deposition, the DC sputtering power of the aluminum target was set to a low 850 W. Then, using the instrument's built-in linear power control program, the aluminum target power was uniformly and linearly increased from 850 W to 1500 W over the next 30-second deposition window. During this process, as the power increased, the sputtering rate and kinetic energy of aluminum atoms increased, and the purity, density, and crystallinity of aluminum in the deposited film gradually improved. Monitoring using online X-ray fluorescence spectroscopy (XRF) confirmed that the aluminum content in the aluminum film increased from approximately 96% initially to nearly 100% on the surface. The final total thickness of the gradient aluminum film was approximately 0.15 μm. Atomic force microscopy (AFM) measurements showed that its surface was extremely smooth, with a root mean square roughness (Rq) of only 0.008 μm. At this point, the complete gradient magnetic sensitive aluminum plating layer was constructed.

[0057] The electroplated aluminum sample prepared in Example 1 was subjected to comprehensive testing: Thermo-magnetic synergistic iridescent optical response performance: Observation was performed using an optical microscope system equipped with a temperature control console and a Helmholtz coil. Without a magnetic field, when the sample was heated from 20°C to 60°C, the color uniformly transitioned from deep blue through blue-green and green to light yellow, with a macroscopic response time of approximately 3 seconds. After applying a steady magnetic field of 200 mT parallel to the film surface, the same temperature rise process was repeated, and the change in reflectance spectrum at the maximum absorption wavelength was measured using a spectrophotometer. The calculated iridescent optical contrast ratio (ΔE*ab) was 75% higher than that without a magnetic field. This indicates that the magnetic field effectively modulated the physical state of the thermosensitive core layer or the orientation of dye molecules through the magnetically sensitive sheath, producing a strong synergistic enhancement effect.

[0058] Infrared stealth anti-counterfeiting verification: A long-wave infrared thermal imager (operating wavelength 8-14 μm) is aimed at the sample. A low-power infrared lamp is used to briefly and non-uniformly illuminate the sample. On the thermal imager screen, a "MATRIX-01" QR code pattern composed of different grayscale areas is clearly displayed. Scanning the pattern on the screen with a mobile phone app achieves a decoding success rate of 99.9%. This feature is completely invisible under normal lighting, providing extremely strong anti-counterfeiting concealment.

[0059] Magnetochromatic optical gloss variation: The gloss (GU) of the aluminum-coated surface was measured using a 60° gloss meter. Without a magnetic field, the average gloss at multiple points was 188 GU. When a 0.6 T neodymium iron boron magnet was brought close to the sample surface (approximately 2 mm), the gloss decreased to 124 GU, a change of 34%. This dynamic gloss change was clearly visible to the naked eye and responded rapidly.

[0060] Heat transfer (hot stamping) performance: Tested on a commercial flatbed hot stamping machine. The substrate was PVC cardboard. The hot stamping head temperature was set to 52℃, the pressure to 0.55 MPa, and the holding time to 0.9 seconds. After hot stamping, the pattern (including iridescent layer 3, barrier layer 4, and aluminized layer 5) was completely and clearly transferred to the PVC surface with sharp, burr-free edges. Release layer 2, along with base layer 1, was completely peeled off and recycled. The coverage rate of the transferred area was calculated using image analysis software, achieving a hot stamping success rate of 99.95%.

[0061] Durability testing: The sample was placed in a constant temperature and humidity chamber and subjected to accelerated aging testing at 85℃ / 85% relative humidity. After 500 hours, the sample was removed, and the degradation of key performance indicators such as iridescent optical response time and contrast ratio, infrared QR code recognition rate, and magnetostrictive gloss change rate was less than 7%, demonstrating excellent environmental stability.

[0062] Comparative Example Structure: 12μm ordinary PET base film / wax hot melt adhesive release layer / gravure printed acrylic resin color layer (containing physically mixed microcapsule thermochromic pigments, color change range 45-65℃) / vacuum evaporated aluminum film.

[0063] Through testing, this comparative example is as follows: Single function: It only has basic temperature change and no magnetic, infrared or other responses, and has the lowest level of anti-counterfeiting.

[0064] Poor performance: slow temperature response (5-10 seconds), low and uneven color contrast. The hot stamping process window is extremely narrow, sensitive to temperature and pressure, the yield is usually below 96%, and the quality of the pattern edges is poor.

[0065] Poor durability: Microencapsulated pigments exposed in resin are prone to leakage and oxidation failure with long-term use, and their temperature change cycle life is usually less than 1000 cycles. The vapor-deposited aluminum film is porous and easily oxidizes and darkens.

[0066] Lack of collaboration and intelligence: The layers are simply stacked, and their performance is independent and even restrictive. The performance of the release layer is fixed, making it impossible to optimize the hot stamping process.

[0067] Through the detailed description of the above embodiments and the stark contrast of the comparative examples, it is fully demonstrated that the temperature-magnetic dual-response anti-counterfeiting holographic optical anti-counterfeiting electroplated aluminum and its preparation process provided by the present invention have the following advantages: Innovation and synergy in structural design: From the five-layer, seven-sublayer structure shown in Figure 1 to the core-sheath fiber shown in Figure 2, each layer is carefully designed to not only perform independent functions, but also to synergize with each other through interfaces and field effects (such as magnetically enhanced iridescent optical response and gradient aluminum film dynamic luster), producing a composite effect that far exceeds the simple superposition of individual functions.

[0068] The anti-counterfeiting system is multi-layered and highly secure: It integrates color-changing effects that are perceptible to the general public, dynamic and visible magneto-optical gloss changes, and infrared invisible information that requires professional equipment to identify. This forms a three-dimensional anti-counterfeiting system that ranges from easy to difficult and from sensory to instrumental, greatly increasing the technical and cost barriers to counterfeiting.

[0069] Advanced and controllable manufacturing process: The integrated process shown in Figure 3 integrates multiple micro-nano manufacturing technologies, achieving precise control from the nanoscale (particles, fibers) to the microscale (channels, membranes), ensuring high consistency and repeatability of product performance, and laying the foundation for large-scale production.

[0070] Product performance excellence and customizability: Example 1 demonstrates the ability to deeply customize in the general high-performance direction, indicating that the technology platform has strong flexibility and wide application adaptability.

[0071] Therefore, this invention not only represents a major technological breakthrough, but also possesses enormous industrialization potential and market application prospects.

[0072] The foregoing description illustrates and describes several preferred embodiments of the present invention. However, as previously stated, it should be understood that the present invention is not limited to the forms disclosed herein and should not be construed as excluding other embodiments. It can be used in various other combinations, modifications, and environments, and can be altered within the scope of the inventive concept described herein through the foregoing teachings or techniques or knowledge in related fields. Any modifications and variations made by those skilled in the art that do not depart from the spirit and scope of the present invention should be within the protection scope of the appended claims.

Claims

1. An iridescent optically security printed electrochemical aluminum characterized in that, The electrochemical aluminum is a multilayer structure stacked in sequence, comprising from bottom to top: a magnetic sensitive enhancement base layer, comprising a modified PET support layer and a three-dimensional network microchannel layer; the modified PET support layer is a graphene modified biaxially stretched PET film; the three-dimensional network microchannel layer is constructed on the surface of the modified PET support layer by a microfluidic molding process, has a three-dimensional interlaced network structure, and the pore size of the microchannel is randomly distributed in the range of 5-20 μm; the three-dimensional network microchannel is filled with nano-sized Fe3O4 magnetic sensitive particles; a dynamic separation layer, which is directly stacked on the three-dimensional network microchannel layer and is composed of a temperature-sensitive phase change fluororesin; the temperature-sensitive phase change fluororesin layer contains a phase change material, which undergoes a phase change at 45-55°C, so that the peeling force of the dynamic separation layer changes adaptively with temperature; a temperature-magnetic composite nanofiber color-changing layer, which is directly stacked on the dynamic separation layer and is in-situ formed by electrospinning process, and can produce color-changing optical effect; the composite nanofiber has a core-sheath structure, wherein the core layer is a temperature-sensitive color-changing core material, and the sheath layer is a magnetic sensitive polymer matrix; the diameter of the nanofiber of the color-changing layer is gradiently distributed in the range of 500-2000 nm; a polyelectrolyte alternately deposited barrier layer, which is directly stacked on the composite nanofiber color-changing layer and is formed by alternately depositing polycation electrolyte and polyanion electrolyte through layer-by-layer self-assembly process, and has embedded infrared stealth identification particles in the alternately deposited structure; a gradient magnetic sensitive aluminum plating layer, which is directly stacked on the barrier layer and comprises a magnetic sensitive transition layer at the bottom and a gradient aluminum film layer at the top; the magnetic sensitive transition layer is doped with CoNiP alloy nanoparticles; the aluminum content of the gradient aluminum film layer increases from the side close to the magnetic sensitive transition layer to the upper surface in the range of 95% to 100%.

2. The iridescent optically secure electrochromic aluminum of claim 1, wherein, The thickness of the modified PET support layer is 25-30 μm, and the doping mass fraction of graphene is 3%-5%; the porosity of the three-dimensional network microchannel layer is 30%-45%, and the particle size of the filled Fe3O4 magnetic sensitive particles is 20-50 nm, the mass fraction of which accounts for 8%-12% of the magnetic sensitive enhancement base layer, and the saturation magnetization is 50-80 emu / g.

3. The iridescent optically secure electrochromic aluminum of claim 1, wherein, The thickness of the dynamic separation layer is 1.5-2.0 μm, which is made of polyvinylidene fluoride-hexafluoropropylene copolymer and 5%-8% mass fraction of polyethylene glycol with a phase change temperature of 48°C; the peeling force of the dynamic separation layer before phase change is 0.5-0.7 N / cm, and the peeling force after phase change is 0.1-0.2 N / cm.

4. The iridescent optically secure electrochromic aluminum of claim 1, wherein, The thickness of the warm-magnetic composite nanofiber color-changing layer is 4-6 μm, and the area density is 8-12 g / m 2 ; wherein the core layer diameter of the core-mantle structure is 200-800 nm, and the mantle layer thickness is 150-600 nm; the magnetic polymer matrix is a blend of polyvinylidene fluoride-hexafluoropropylene copolymer and Fe3O4 nanoparticles, and the mass fraction of Fe3O4 is 10%-15%.

5. The iridescent optically security electricized aluminum of claim 4, wherein, The temperature-sensitive color-changing core material in the core layer of the composite nanofiber is an N-isopropyl acrylamide-maleic anhydride copolymer grafted color-changing dye, and the color-changing optical response interval is continuously adjustable in the range of 12-75°C; under the action of a magnetic field of 100-300 mT, the color-changing optical contrast of the composite nanofiber color-changing layer is increased by ≥50%.

6. The iridescent optically secure electrochemical aluminum of claim 1, wherein, The thickness of the polyelectrolyte alternately deposited barrier layer is 2.0-3.5 μm, the number of layers of the polycation electrolyte and the polyanion electrolyte alternately deposited is 15-25 layers; the polycation electrolyte is polyallylamine hydrochloride, and the polyanion electrolyte is sodium polystyrene sulfonate; the infrared stealth identification particles are antimony-doped tin oxide nanoparticles with a particle size of 80-150 nm, which have a specific absorption peak in the 8-14 μm infrared wave band, and the mass fraction is 3%-6%.

7. The iridescent optically secure electrochemical aluminum of claim 1, wherein, In the gradient magnetic sensitive aluminum plating layer: The thickness of the magnetic sensitive transition layer is 0.05-0.1 μm, wherein the particle size of the CoNiP alloy nanoparticles is 10-30 nm, and the mass fraction is 8%-12%; The thickness of the gradient aluminum film layer is 0.12-0.18 μm, the surface roughness Ra is ≤0.008 μm, and the density is ≥99.9%; under the action of a magnetic field of 0.3-0.8 T, the iridescent metal luster reflectivity change of the gradient aluminum film layer is ≥30%.

8. The iridescent optically secure electrochemical aluminum of claim 1, wherein, The temperature-magnetic composite nanofiber iridescent layer of the electrochemical aluminum can produce continuous iridescent color change in the temperature range of 12-75℃, the response time is ≤4 s, and the number of repeated color changes is ≥6000 times.

9. The iridescent optically security-electrochromic aluminum of claim 6, wherein, The infrared stealth identification particles are arranged in the barrier layer to form a preset pattern, which can be identified as a two-dimensional code under an infrared thermal imager, and the identification accuracy is ≥99%.

10. A production process for manufacturing the iridescent optically security anticounterfeiting electrochemical aluminum according to any one of claims 1-9, characterized in that, The steps are as follows: Step S1: providing a graphene modified PET substrate, carrying out plasma-ultraviolet composite pretreatment to obtain a pretreated substrate with a surface contact angle ≤20°; Step S2: preparing a three-dimensional network microchannel on the surface of the pretreated substrate by a microfluidic in-situ forming process, then filling the microchannel with a Fe3O4 magnetic sensitive particle dispersion liquid, and forming the magnetic sensitive enhancement substrate layer after vacuum drying and solidification; Step S3: coating a temperature-sensitive phase change fluororesin slurry on the magnetic sensitive enhancement substrate layer, and forming the dynamic detachment layer after segmented thermal curing; Step S4: using a coaxial electrospinning process, co-spinning an outer layer spinning liquid containing a magnetic sensitive polymer matrix and an inner layer spinning liquid containing a temperature-sensitive color-changing core material on the dynamic detachment layer, and forming the temperature-magnetic composite nanofiber iridescent layer after heat setting; Step S5: alternately depositing a polycation electrolyte solution and a polyanion electrolyte solution containing infrared stealth identification particles on the iridescent layer by a layer-by-layer self-assembly process to form the polyelectrolyte alternately deposited barrier layer; Step S6: using a magnetron sputtering process, first depositing a magnetic sensitive transition layer doped with CoNiP alloy nanoparticles on the barrier layer, and then depositing a gradient aluminum film layer with a gradient change in aluminum content by controlling the gradient change of the sputtering power, thereby forming the gradient magnetic sensitive aluminum plating layer, and obtaining the finished electrochemical aluminum after winding.